Trends, Contributions and Prospects: Bibliometric Analysis of ANOVA Research in 2022-2023 - Sutrisno, Utis; Wulandari, Yulia; Usep; Arifin, Samsul; Roni; Manurung, Monica Mayeni; Faisal, Muhamad (Indonesian Journal of Applied Mathematics and Statistics, 2024)
This study aims to analyze the development and contribution of research on the topic of ANOVA (Analysis of Variance) using the bibliometric analysis method. ANOVA is a statistical method used to compare the means of three or more groups. Through bibliometric analysis, we explore articles published in journals related to ANOVA within a certain time span, namely 2022-2023. The method of bibliometric analysis involves collecting bibliographic data from relevant sources and analyzing characteristics such as frequency of publication, notable authors, and most frequently cited journals. This study uses a bibliometric analysis method that retrieves 1,911 metadata from Scopus. The results of the bibliometric analysis revealed an increase in the number of publications about ANOVA during the time span studied, namely 2022-2023. These findings indicate that ANOVA remains a relevant and interesting topic for researchers in various disciplines. In addition, there is a wide variety of research topics related to ANOVA, including the use of ANOVA in various contexts, such as laboratory experiments, clinical research, and analysis of survey data. By analyzing the contribution of research on the topic of ANOVA, this study provides valuable insights for us. Moreover, the researcher also discussed prospects for future research on this topic, including the development of new analytical methods and the wider application of ANOVA in various scientific and practical contexts.